On fatigue behaviour of two spring steels. Part II: Mathematical models (Fracture and Structural Integrity, 2016)
Symmetric fatigue in two spring steels is investigated in three groups of specimens. One of the groups (Steel EN10270-1SH/ DIN 17223C – C 0.82%, Mn 0.76%, Si 0.26%) has experienced rotating-bending fatigue in air, and the other two groups (Steel BS250A53/ DIN 55Si7 – C 0.56%, Mn 0.81%, Si 1.85%), torsion fatigue in-air and corrosion environment. All experiments include testing to fracture, applying acetate-foil replication technique, replica monitoring of short crack surface growth, length measuring of propagating cracks, a, at the corresponding number of fatigue cycles, N. Data obtained from replica monitoring are presented in plots “Crack lengths, a – Cycles, N”, and used for calculating fatigue crack growth rates, da/dN, and graphical presentations “Crack growth rates, da/dN – Crack lengths, a”. A mathematical description of da/dN – a is presented by introducing a parabolic-linear model in different versions for each of the steels. The model versions are verified through comparing the experimental fatigue lifetimes with those calculated by the proposed model version.
Keywords: Rotating-Bending Fatigue; Torsion fatigue; Short Fatigue-Cracks; Modeling of Crack-Growth rate